2017
DOI: 10.18415/ijmmu.v4i6.122
|View full text |Cite
|
Sign up to set email alerts
|

Sustaining the Entrepreneurship in Rural Tourism Development

Abstract: Entrepreneurs play an important role in sustaining rural tourism and formulation of sustainable strategies being the initiators of the tourism business and the engine of the local development. Therefore, it is necessary to stimulate the development of entrepreneurial activities for the recovery of rural tourism potential and regional traditions, maintaining local employment growth and increase living standards in line with identifies needs and priorities of regional human resources development. This article ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…The study of Kurnia et al (2018) found that the development of an entrepreneurial spirit among young people, especially students, is urgent to change their mindset to make new ideas or innovations and then develop them into businesses. Sharif and Lonik's (2017) study found that entrepreneurship is considered significant benefits for rural tourism. The absence of entrepreneurship can pose a significant obstacle to economic development and the workforce's revitalization affected by the restructuring.…”
Section: Introductionmentioning
confidence: 99%
“…The study of Kurnia et al (2018) found that the development of an entrepreneurial spirit among young people, especially students, is urgent to change their mindset to make new ideas or innovations and then develop them into businesses. Sharif and Lonik's (2017) study found that entrepreneurship is considered significant benefits for rural tourism. The absence of entrepreneurship can pose a significant obstacle to economic development and the workforce's revitalization affected by the restructuring.…”
Section: Introductionmentioning
confidence: 99%
“…Most youth believe they can affect small changes at the community level in the Malaysian context, while just a minority believe the contrary (Samsuddin et al, 2018). In most developing countries, including Malaysia, youth living in rural areas are involved with local natural resource-based jobs (Zeinab et al, 2016;Tuomas et al, 2016;Md Sharif & Tuan Lonik, 2017). The strategy adopted by the Government of Malaysia to eradicate poverty is modernization to increase efficiency, productivity, production, and returns to farmers and fishers (Alex, 1980;Rozhan, 2017).…”
Section: Rural Development and Youth Local Championsmentioning
confidence: 99%
“…Rural development is one aspect of national planning that aims to achieve sustainable development by improving the quality of life of local communities (Md Sharif & Tuan Lonik, 2017). Rural development has become a concern worldwide because of the enormous gap between urban and rural developments (Kamarudin et al, 2012;Manggat, 2018;Rashid et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, for this scenario to be viable, the participation of the State, the private sector and educational institutions is required, so that effective strategies can be designed in favor of these ends. In addition to the above, [7] address this issue from the perspective of the tourism sector, for which they affirm that entrepreneurs play an important role in the maintenance of rural tourism and the formulation of sustainable strategies, being the engine of local development These premises acquire special interest in the Mexican context, considering that, as mentioned by [8], the tourism sector contributes 8.8% of the gross domestic product (GDP) of our country, produces about 4 million direct jobs and generates a favorable balance in the sector balance above 11,000 million US dollars. However, it also highlights that, despite the dynamism of the Mexican tourism sector, in the five main states in this area about 27% of its inhabitants are in a situation of poverty, which leads to another series of evils or lags in education, health and employment.…”
Section: Introductionmentioning
confidence: 99%